Peran Mikrobioma dalam Kesehatan Manusia : Perspektif Baru dalam Pengobatan - Syamsul, Muhammad; Adzim, Pauzan; Mardan, Kamil (Journal of Science and Technology: Alpha, 2025)
The microbiome, a collection of microorganisms living within the human body, plays a crucial role in maintaining health and physiological balance. Recent research indicates that the microbiome not only acts as a defense mechanism against pathogens but also contributes to metabolism, the immune system, and neurological functions. This article explores the role of the microbiome in various aspects of human health, including its relationship with chronic diseases such as diabetes, obesity, autoimmune disorders, and neuropsychiatric conditions. Additionally, microbiome-based therapeutic approaches, such as fecal microbiota transplantation and probiotics, have demonstrated significant potential in disease treatment. With an increasingly deep understanding of the microbiome, personalized medicine approaches are becoming more feasible, paving the way for more effective and targeted treatments. This article highlights the importance of the microbiome as a new perspective in modern medicine and the need for further research to optimize its application in clinical practice.